Colorado wolves: informational package - Colorado State University. Center for Human-Carnivore Coexistence (CHCC), author; Center for Collaborative Conservation, compiler; Colorado State Unviersity. Extension, publisher (Colorado State University. Libraries, 2020)
Included herein are the 12 Information Sheets that comprise the Colorado Wolves series. These Information Sheets are intended to educate the public and inform science-based policy but are not intended to state a position on any particular policy decision.
Date taken from website.
Keywords: Wolves -- Colorado; Wolves -- Reintroduction -- Colorado